"Equal Opportunity Violence": Hope Solo and the Rhetoric of Domestic Violence in Sports Media. Issue 2 (3rd April 2019) - Chase, Alexandria R.
Abstract: In 2014, American soccer player Hope Solo was accused of domestic violence. Controversy over Solo's participation in the upcoming 2015 Women's World Cup tournament flooded news and sports media. Most interestingly for scholars of gender and communication, these conversations equated Solo with National Football League (NFL) players, such as Ray Rice and Adrian Peterson, who had also been accused of domestic violence and punished to varying degrees. This discourse both forwarded claims of reverse discrimination and rhetorically masculinized Solo to fold her into normative gendered understandings of violence. The effect was a discursive degendering of violence. This article is concerned with the way that gender and violence are made sense of in sports discourse. I argue that coverage of Solo—specifically, the discourses that tether her to what appear to be her male counterparts and the resulting sense of gender equality—alters cultural understandings of gender and violence in dangerous ways.